Chronic Kidney Disease Exacerbates Myocardial Ischemia Reperfusion Injury: Role of Endoplasmic Reticulum Stress-Mediated Apoptosis. Issue 6 (June 2018) - Guo, Junjie; Zhu, Jianbing; Ma, Leilei; Shi, Hongtao; Hu, Jiachang; Zhang, Shuning; Hou, Lei; Xu, Fengqiang; An, Yi; Yu, Haichu; Ge, Junbo
Abstract : ABSTRACT: Chronic kidney disease (CKD) is known to exacerbate myocardial ischemia reperfusion (IR) injury. However, the underlying mechanisms are still not well understood. Despite various strategies for cardioprotection, limited studies have been focused on the prevention of CKD-induced myocardial susceptibility to IR injury. Here, we hypothesized that excessive endoplasmic reticulum (ER) stress-mediated apoptosis involved in myocardial IR injury in CKD mice and pretreatment with chemical ER chaperone rendered the heart resistant to myocardial IR injury in the setting of CKD. CKD was induced by 5/6 subtotal nephrectomy (SN) in mice, whereas sham-operated mice served as control (Sham). CKD significantly aggravated the cardiac injury after IR in SN group than Sham group as reflected by more severe cardiac dysfunction, increased myocardial infarct size and the ratio of myocardial apoptosis. The expression of ER stress-mediated apoptotic proteins (Bcl-2 associated X protein (Bax), glucose-regulated protein 78 (GRP78), CCAAT/enhancer-binding protein homologous protein (CHOP), caspase-12) was markedly upregulated after IR injury in SN group than Sham group, whereas the expression of anti-apoptotic protein, Bcl-2, was obviously downregulated. In addition, the chemical ER chaperone sodium 4-phenylbutyrate (4PBA) pretreatment ameliorated cardiac dysfunction and lessened the infarct size and myocardial apoptosis after IR injury in mice with CKD. Taken together, these findings demonstrated that excessive activation of ER stress-mediated apoptosis pathway involved in the CKD-induced myocardial susceptibility to IR injury, and chemical ER chaperone 4PBA alleviated myocardial IR injury in mice with CKD.